The changing concept of radiographer's role in UAE: An analysis of radiologists' opinions and acceptance. Issue 4 (November 2022) - Abuzaid, M.M.; Elshami, W.; Kadhom, M.; McConnell, J.; Mc Fadden, S.
Abstract: Introduction: The role of radiographers in the United Arab Emirates (UAE) is currently focused on image acquisition. However, many advances have been made in different countries in recent years whereby radiographers who receive appropriate education and training, can provide image interpretation/reports. When implemented, this role development has enabled a more cost effective and efficient service delivery whilst relieving the burden off radiologists, allowing them to concentrate on more complex imaging examinations. This role development is commonplace in many countries but not in the UAE. Aim: This study aims to investigate the radiologists' opinions, perceptions, and willingness to accept the advanced practice role of reporting radiographers in the UAE and determine their level of support for implementing these roles. Methods: Data was collected utilizing a mixed-methods study design that included a survey and focus group discussions (FGD). Study participants included radiologists who currently work in UAE public and private health organizations. The survey link was emailed directly to the radiologists, together with a covering letter and participants' information sheet outlining the study's aim. Participants indicated on the survey if they wanted to participate in FGD. Two online FGD were conducted using Zoom software (Zoom Video Communications Inc., San Jose, California, United States) and aimed to explore possible reasons for participant's opinions. Ethical approval was obtained from the Ministry of Health, and all methods were performed as per study protocol. Results: A total of 69 radiologists participated in the survey, 48 males and 21 females aged between 41 and 60 years and with between 11 and 16 years of experience. Most participants (n = 54, 78.2%) believe that radiographers should only perform advanced tasks in image interpretation after obtaining adequate training and under the supervision of a radiologist. According to 55% of radiologists, the development of the radiographer role could draw more UAE nationals to the field. Six participants were recruited to FGD and declared mixed opinions that emphasized the need to improve the radiographers knowledge and experience to enable role development. Conclusion: Radiologists' worries about radiographer engagement in image interpretation may be alleviated if they participate in education and training for new responsibilities. In addition, this could boost the confidence of radiologists and improve trust in radiographer competency and training. Implications for practice: Guidelines and work standards must be developed jointly by radiologists and radiographers to ensure the governance and acceptability of new radiographer reporting roles. Some radiologists perceive that radiographer reporting is possible in UAE when radiographers are trained to set guidelines and with supervision from radiologists. Change is taking place, and many radiologists express optimism for the future, though the rate of change will be determined by a willingness to change attitudes and perceptions.